Footstrike is the major cause of hemolysis during running - Telford, R. D.; Sly, G. J.; Hahn, A. G.; Cunningham, R. B.; Bryant, C.; Smith, J. A. (Journal of Applied Physiology, 2002)
There is a wide body of literature reporting red cell hemolysis as occurring after various forms of exercise. Whereas the trauma associated with footstrike is thought to be the major cause of hemolysis after running, its significance compared with hemolysis that results from other circulatory stresses on the red blood cell has not been thoroughly addressed. To investigate the significance of footstrike, we measured the degree of hemolysis after 1 h of running. To control for the potential effects of oxidative and circulatory stresses on the red blood cell, the same subjects cycled for 1 h at equivalent oxygen uptake. Our subjects were 10 male triathletes, who each completed two separate 1-h sessions of running and cycling at 75% peak oxygen uptake, which were performed in random order 1 wk apart. Plasma free hemoglobin and serum haptoglobin concentrations were measured as indicators of hemolysis. We also measured methemoglobin as a percentage of total hemoglobin immediately postexercise as an indicator of red cell oxidative stress. Plasma free hemoglobin increased after both running (P < 0.01) and cycling (P < 0.01), but the increase was fourfold greater after running (P < 0.01). This was reflected by a significant fall in haptoglobin 1 h after the running trials, whereas no significant changes occurred after cycling at any sample point. Methemoglobin increased twofold after both running and cycling (P < 0.01), with no significant differences between modes of exercise. The present data indicate that, whereas general circulatory trauma to the red blood cells associated with 1 h of exercise at 75% maximal oxygen uptake may result in some exercise-induced hemolysis, footstrike is the major contributor to hemolysis during running.